The potential application of sulfonated polystyrene (SPS) from recycled styrofoam in the reduction of heavy metals -Ba+2, Cd+2, Cr+3, Pb+2 and Ni+2 in wastewater - Manalac, Sharon M. (2007)
This study investigates the potential of using sulfonated polystyrene (SPS) from recycled styrofoam in the reduction of heavy metals - Ba+2, Cd+2, Cr+3, Pb+2 and Ni+2, in wastewater.
Clean and contaminated polystyrene were sulfonated with concentrated sulfuric acid and used in a simple batch ion exchange process. The leaching property of the SPS was also evaluated using the Environmental Protection Agency (EPA) Method 1131 or the Toxicity Characteristics Leaching Procedure (TCLP).
Experimenental results from the sulfonation process yielded an average ion exchange capacity value of 10.3 ± 5.05 x 10-4 Mol /gSPS for clean SPS as compared to 15.0±7.61 x 10-4 mol/gSPS for contaminated SPS, and the degree of sulfonation, calculated as percent sulfonation has an average value of 11.98 ± 6.53% for clean SPS as compared to 18.41±11.44% for contaminated SPS. These values indicate that the method of sulfonation employed was able to introduce sulfonate groups both for the clean and contaminated polystyrene with apparent greater effectivity for the contaminated polystyre
In the batch ion exchange process, the following values for percentage removal of heavy metals were obtained: clean SPS from a low value of 2.27% for cadmium to a high value of 35.81% for barium, for contaminated SPS- from a low value of 15.21% for chromium to a high value of 86.13% for bari
Based on the above results, the utilization of waste polystyrene as an alternative ion exchange resin may provide a solution to minimize the solid waste problem and at the same time reduce the heavy metal concentration usually found in landfill leachate, thus closing the loop between the solid waste and wastewater problem in a landfi
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Polystyrene; Sulfonation; Sewage -- Purification -- Heavy metals removal